Study on the influence of calculation domain on the accuracy of CFD simulation of power transmission tower aerodynamic coefficient - Li Wei; Li Zhipeng; Zhang Xueli; Huang Guo (E3S Web of Conferences, 2023)
Wind load is the control load in the design of power transmission tower. The shape coefficient of that can be obtained by CFD. Small calculation domain can affect the calculation accuracy, and large one can reduce the calculation efficiency. In this paper, the calculation domains with different sizes are designed to optimize the calculation domain size.